Delayed Initiation of ECMO Is Associated With Poor Outcomes in Patients With Severe COVID-19: A Multicenter Retrospective Cohort Study - Li, Xuyan; Hu, Ming; Zheng, Ruiqiang; Wang, Yishan; Kang, Hanyujie; Jiang, Li; Zhong, Ming; Sang, Ling; Zheng, Xia; Pan, Chun; Zhang, Wei; Qiu, Haibo; et al. (Frontiers in Medicine, 2021)
Background Extracorporeal membrane oxygenation (ECMO) is a rapidly evolving therapy for acute lung and/or heart failure. However, information on the application of ECMO in severe coronavirus disease 2019 (COVID-19) is limited, such as the initiation time. Especially in the period and regions of ECMO instrument shortage, not all listed patients could be treated with ECMO in time. This study aims to investigate and clarify the timing of ECMO initiation related to the outcomes of severe COVID-19 patients. The results show that ECMO should be initiated within 24 hours after the criteria are met. Methods In this retrospective, multicenter cohort study, we enrolled all ECMO patients with confirmed COVID-19 at three hospitals between Dec 29, 2019, and Apr 5, 2020. Data on the demographics, clinical presentation, laboratory profile, clinical course, treatments, complications and outcomes were collected. The primary outcomes were successful ECMO weaning rate and 60-day mortality after ECMO. Successful weaning from ECMO means that the patient's condition improved with adequate oxygenation and gas exchange, as shown by the vital signs, blood gases, and chest X-ray, and the patient was weaned from ECMO for at least 48 hours. Results A total of 31 patients were included in the analysis. The 60-day mortality rate after ECMO was 71%, and the ECMO weaning rate was 26%. Patients were divided into a delayed ECMO group (3 [IQR, 2–5] days) and early ECMO group (0.5 [IQR, 0–1] days) based on the time between meeting the ECMO criteria and ECMO initiation. Fourteen and seventeen patients were included in the early and delayed treatment groups, respectively. Early initiation of ECMO was associated with decreased 60-day mortality after ECMO (50% vs. 88%, P=0.044) and an increased ECMO weaning rate (50% vs. 6%, P=0.011). Conclusions In ECMO-supported COVID-19 patients, delayed initiation of ECMO is a risk factor associated with a poorer outcome.